The paradox of repression and nonviolent movements - Kurtz, Lester R.; Smithey, Lee A.; Martin, Brian, 1947- (Syracuse studies on peace and conflict resolution., 2018)
This volume brings together distinguished scholars and esteemed practitioners from around the world to reflect on and present empirical case studies that expose the political, social, and psychological underpinnings of the paradox of repression.--description provided by publisher.